Open University for the Elderly: An experience report in a times of pandemic - Simões Cordeiro, Monique; Andrade de Oliveira, Cenira; Renata Rodrigues M. A. Viana, Dayane; Pinto Medina, Fernanda; Henrique Durante Cirne Nascimento, Octávio; Soares Tavares de Oliveira, Pedro Augusto; Aleixo da Silva, Rayane (Guará Journal, 2024)
This article presents the report of an experience about activities developed by the Universidade Federal do Espírito Santo (UFES) Extension Program Universidade Aberta à Pessoa Idosa (UnAPI), in the year 2021, a period marked by the COVID-19 pandemic. Due to the necessary social isolation as a health protection measure, UnAPI dared to reinvent itself and launch anonline version, aiming to maintain contact with the elderly who frequent the program, in order to mitigate the effects of social isolation imposed by the situation. Thus, we sought to analyze the contribution of the Extension Program to the quality of life of elderly people in the most intense period of the pandemic. As a result, it was possible to identify a decrease in the level of suffering caused by the individual and collective social isolation of the elderly. From the systematic interactivity (albeit virtual) with this audience, it was possible to increase the quality of life of these people who, at the height of the pandemic, were emotionally fragile.
Keywords: Extension; Pandemic; Elderly; University Open to the Elderly